THE EFFECTIVENESS OF USING ANIMATION MEDIA IN RESPIRATORY SYSTEM LEARNING IN CLASS VIII OF SMPIT ROBBANI RANTAUPRAPAT - Marliana; Rahmi Nazliah; Rosmidah Hasibuan (RADJA PUBLIKA, 2025)
Learning is a process of interaction between students, educators, and learning resources in an educational environment to achieve certain goals. This study aims to examine the effect of using animation media in learning the respiratory system on the completeness of learning outcomes of class VIII students of SMPIT Robbani Rantauprapat. This study uses an experimental design by comparing two groups, namely the experimental class using animation media and the control class using conventional methods. The purpose of this study was to determine the effectiveness of animation media in improving student understanding and to compare student learning outcomes between the two methods. The results showed that the completion of student learning outcomes in the experimental class using animation media reached 94.28%, while in the control class it only reached 42.85%. The discussion of these results indicates that animation media can significantly improve student understanding compared to traditional lecture methods. In conclusion, the use of animation media in learning the respiratory system is very effective in improving the completion of student learning outcomes. This study suggests the use of animation media as an interesting and effective learning alternative.